Creating a Eurasian Union Economic Integration of the Former Soviet Republics - Vymyatnina, Yulia. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Creating a Eurasian Union offers a detailed analysis of the economies of the Customs Union of Russia, Belarus, and Kazakhstan and the proposed Eurasian Union. The authors employ econometric analysis of business cycles and cointegration analysis to prove the fragility of the union's potential economic success. By providing a brief description of the economic integration of the former Soviet republics, this pioneering work analyses the on-going trial and error processes of market integration led by Russia. Vymyatnina and Antonova's distinctive argument is the first consistent analysis of the emerging Eurasian Union. They incorporate both a non-technical summary of the integration process and previous research and analytical comments, as well as a thorough empirical analysis of the real data on the economic development of the participating countries, to caution that the speed of integration might undermine the feasibility of the Eurasian Union.